2007
DOI: 10.1007/s00455-007-9127-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the 3-ounce Water Swallow Test

Abstract: The 3-ounce water swallow test is frequently used to screen individuals for aspiration risk. Prior research concerning its clinical usefulness, however, is confounded by inadequate statistical power due to small sample sizes and varying methodologies. Importantly, research has been limited to a few select patient populations, thereby limiting the widespread generalizability and applicability of the 3-ounce test. The purpose of this study was to investigate the clinical utility of the 3-ounce water swallow test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
285
0
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(309 citation statements)
references
References 29 publications
6
285
0
18
Order By: Relevance
“…The sample size ranged from 25 to 3,000 participants. The article with 3,000 participants (32) reported a very heterogeneous population, with individuals of both genders, aged between 2 and 105 years, and with various pathologies. Chart 2 shows the characteristics relating to the underlying pathology for each study population selected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size ranged from 25 to 3,000 participants. The article with 3,000 participants (32) reported a very heterogeneous population, with individuals of both genders, aged between 2 and 105 years, and with various pathologies. Chart 2 shows the characteristics relating to the underlying pathology for each study population selected.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, a failure in one of the issues analyzed indicates a risk for swallowing disorders. There are also studies (26,30,32) that used instruments that involved only the swallowing test with water for screening. In these studies, the patient had to ingest the liquid and some signs were observed during and after the intake.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This enabled information on both oral and pharyngeal stage deficits to be compiled. The CSE consisted of a patient interview, visual examination of the oromusculature, oromotor examination, perceptual evaluation of voice quality, and a series of oral intake trials of fluids and foods that also included a water swallow test [14][15][16][17] when appropriate. All participants were trialled with the fluids/foods considered to be least normal first (i.e., extremely thick fluids, puree diet), with progression towards normal dietary consistencies and textures (i.e., thin fluids, general diet), during oral intake trials if appropriate.…”
Section: Methodsmentioning
confidence: 99%